Psiholoģiskā līguma starp darbinieku un darba devēju saistība ar darbinieku efektivitāti. - Elksne, Sarmīte (Latvijas Universitāte, 2007)
Pētījuma mērķis ir noskaidrot, cik lielā mērā psiholoģiskā līguma rādītāji spēj prognozēt darbinieka darba izpildi. Psiholoģiskā līguma pētīšanai tika izmantota Psiholoģiskā līguma aptauja (Rousseau, 2000). Darbinieku darba izpildes mērīšanai tiks izmantots objektīvs rādītājs – tirdzniecības pārstāvju saņemtās kopējās gada prēmijas, kas tiešā veidā ir atkarīgas no viņu pārdošanas rezultātiem. No rezultātiem var secināt, ka tirdzniecības darbinieku saņemtās prēmijas pēc pārdošanas rezultātiem neietekmē viņu esošās gaidas no darba devēja un tas, vai darba devējs šīs gaidas apmierina. Tātad nevar apgalvot, ka palielinoties atbilstībai starp darbinieku gaidām un to, ko darba devējs sniedz, palielināsies viņu pārdošanas rezultāti – viņu darba izpilde. Lai gan regresijas modelis kopumā nav statistiski nozīmīgs, tomēr darbinieka līdzsvara līguma rādītājs nelielā, bet statistiski nozīmīgā mērā izskaidro atkarīgo mainīgo.

The aim of research is to identify to what extent psychological contract scales prognosticate employee job performance. The author has chosen this as her Masters degree topic as psychological contracts in Latvia are still a relatively new phenomenon within organizations amongst employees and employers and leads to employee/employer relationship quality. However, in stark contrast, in Europe and America, the development and impact of psychological contracts has been studied since the 1960’s. In particular, it was decided to analyze this phenomenon in conjunction with employee job performance since that is the main criterion of interest to employers company profit. The participants in this research are 40 sales representatives from one company. The analysis of psychological contracts uses the psychological contract survey (Rousseau 2000) which will be supplemented by open questions about psychological contract content supported by theory that is proposed by the analysis quality control section. Measuring employee job performance will use objective indicator – sales representatives paid annual bonuses which have been calculated based on sales results. To answer this research questions, multiple regression statistical method was used. Independent variables were defined, along with psychological contract scales and conditional dependent variable - employee job performance measures. In summary form, the regression model is meaningless so existing employee expectations from the employer and whether the employer satisfies these expectations did not influence sales representatives paid bonuses after sales results. Therefore, it is not possible to assert that increased conformity between employee expectations and that what the employer provides, will actually yield higher sales results and thus employee job performance. Although the regression model in summary is not statistically meaningful, although employee psychological contract balanced scale to a small extent do describe dependent variables.
Psychological Agreement between Employee and Employer and Employee Effectiveness
Keywords: Psiholoģija